Evaluation of key parameters for developing a Metarhizium rileyi‐based biopesticide against Spodoptera frugiperda (Lepidoptera: Noctuidae) in maize: laboratory, greenhouse, and field trials. Issue 3 (4th December 2021) - Faria, Marcos; Souza, Daniela Aguiar; Sanches, Marcio Martinello; Schmidt, Francisco Guilherme Vergolino; Oliveira, Charles Martins; Benito, Norton Polo; Lopes, Rogerio Biaggioni
Abstract: BACKGROUND: The entomopathogenic fungus Metarhizium rileyi is known to cause natural infections in some caterpillars. In this multiyear study, we carried out laboratory, greenhouse and three field trials with the aim of developing a sustainable option for control of the fall armyworm (FAW) in maize. Association of M. rileyi with Spodoptera frugiperda baculovirus (SfMNPV) and delivery strategies were also investigated. RESULTS: The selected isolate (CG381) was effective in the laboratory at a low concentration ( 4 × 10 3 conidia cm −2 ), killing >95% of FAW larvae within 8 days. In the greenhouse assay, applications of conidia suspended in water or as dry powder in maize whorls ( 6.3 × 10 6 conidia per plant) produced similar larval mortalities (88%–96%). In the field trials, conventional spraying of unformulated conidia (0.6 and 1.2 × 10 12 conidia ha −1 ) caused low larval mortalities (27–31%). Simultaneous application of either unformulated or oil‐based formulations of M. rileyi conidia and S. frugiperda baculovirus (SfMNPV) to plant rows caused larval mortalities comparable with each of the pathogens applied alone. However, when a formulation containing both pathogens was sprayed directly into the whorls, the overall mortality of S. frugiperda larvae due to pathogens (mostly to M. rileyi infections) reached 59%, twofold higher than the other treatments with conventional spraying, whereas in the control, the overall mortality was only 1%. CONCLUSION: Optimizing exposure of S. frugiperda larvae to an inoculum of virulent entomopathogens through directed applications to maize whorls is critical to produce satisfactory mortality levels and is promising for integrated pest management. Abstract : Our findings highlight the importance of selecting high virulent fungal strains and developing new delivery strategies to significantly increase the performance of biopesticides aimed at Spodoptera frugiperda control in maize. © 2021 Society of Chemical Industry.